Glycinergic Signaling in Macrophages and Its Application in Macrophage-Associated Diseases - Gan, Zhending; Zhang, Meiyu; Xie, Donghui; Wu, Xiaoyan; Hong, Changming; Fu, Jian; Fan, Lijuan; Wang, Shengyi; Han, Sufang (Frontiers in Immunology, 2021)
Accumulating evidence supports that amino acids direct the fate decision of immune cells. Glycine is a simple structural amino acid acting as an inhibitory neurotransmitter. Indeed, glycine receptors as well as glycine transporters are found in macrophages, indicating that glycine alters the functions of macrophages besides as an inhibitory neurotransmitter. Mechanistically, glycine shapes macrophage polarization via cellular signaling pathways (e.g., NF-κB, NRF2, and Akt) and microRNAs. Moreover, glycine has beneficial effects in preventing and/or treating macrophage-associated diseases. Collectively, this review highlights the conceivable role of glycinergic signaling for macrophage polarization and indicates the potential application of glycine supplementation as an adjuvant therapy in macrophage-associated diseases.